2012
DOI: 10.1128/mcb.00356-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of LAT in the Granule-Mediated Cytotoxicity of CD8 T Cells

Abstract: Linker for activation of T cells (LAT) is a transmembrane adaptor protein that is essential to bridge T cell receptor (TCR) engagement to downstream signaling events. The indispensable role of LAT in thymocyte development and T cell activation has been well characterized; however, the function of LAT in cytotoxic-T-lymphocyte (CTL) cytotoxicity remains unknown. We show here that LAT-deficient CTLs failed to upregulate FasL and produce gamma interferon after engagement with target cells and had impaired granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…These changes could reflect selection of particular T cell clones that occurs over the 4-week period in the LAT Y136F model with a diverse TCR repertoire. LAT protein turnover takes 4 days (Ou-Yang et al, 2012), therefore one week of tamoxifen treatment effectively results in 3 days of LAT NEG or LAT Y136F . In search of the immediate and direct effects of LAT perturbation in naïve CD4 T cells, we focused on this short period of LAT perturbation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could reflect selection of particular T cell clones that occurs over the 4-week period in the LAT Y136F model with a diverse TCR repertoire. LAT protein turnover takes 4 days (Ou-Yang et al, 2012), therefore one week of tamoxifen treatment effectively results in 3 days of LAT NEG or LAT Y136F . In search of the immediate and direct effects of LAT perturbation in naïve CD4 T cells, we focused on this short period of LAT perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…FasL is also a target of Egr transcription factors (Rengarajan et al, 2000) and we found Egr-1 , Egr-2 , and Egr-3 expressed at reduced levels in T cells with perturbed LAT function (Figure 2B). LAT Y136F T cells fail to upregulate FasL in response to TCR engagement (Ou-Yang et al, 2012; Sommers et al, 2002). The transcription factor Irf4 has received a lot of interest as a T cell fate-determining factor (Biswas et al, 2010; Huber and Lohoff, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cre-mediated deletion results in the expression of a non-functional LAT-GFP fusion protein, thus accurately marking T cells with the lat gene deleted (16). We crossed ERCreLAT f/f , OT-I TCR transgenic, and LAT −/− mice to generate ERCre + LAT f/− OT-Imice in which only one floxed allele needs to be deleted (17). With tamoxifen treatment, the lat gene can be inducibly deleted in OT-I cells in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that blocking Tim-3 using the antagonistic antibody, 2E2, resulted in significantly more conjugates that had “stable” synapses. Initial proximal TCR signaling, such as Lck phosphorylation and subsequent downstream signaling to LAT, is required for stable synapse formation [41], further providing evidence that Tim-3 is involved in TCR proximal signaling. While the exact mechanism of how Tim-3 effects proximal signaling is still under investigation, our work provides preliminary evidence that Tim-3 may be involved in Lck regulation.…”
Section: Discussionmentioning
confidence: 99%